The experience of a pioneer research program in architecture in Évora - Salema, Sofia (2014)
Three years ago the University of Évora implemented a research PhD program in architecture. Generally a doctorate of architecture has been an academic title awarded to architects who present a theoretical dissertation; however, for us as a young but promising school of architecture it was just natural that a project (as a methodology, a process of knowledge or simulation of a hypothesis) could be part of an advance research in architecture. Thus, we started with this doctoral program seeking to question the current model of PhD programs and established a new pioneering paradigm syllabus in the national context with the intention to reach the international arena During the course syllabus the project lab integrates the formulation of a theoretical hypothesis (a conjecture), that becomes an architectural design, which is unique, but simultaneously an universal knowledge. The program has already two editions were PhD students have been encouraged to develop advance research and fostered interaction between the theoretical and architecture production. No research is yet finished. Students, although much interested in this type of research, are divided in their approach to architecture as a theoretical, speculative and critical field, and architecture as a field of research. Students and teacher are interested in research that develops their architecture design skills, as a relevant process of advancement knowledge in architecture. We believe that PhD syllabus will contribute to demystify and implement the concept of advanced studies in architecture based on architectural research. This paper will share some of the ideas, doubts, and results of our PhD program.